2013
DOI: 10.1111/febs.12190
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the Rhizoctonia solani agglutinin reveals a domain‐swapping dimeric assembly

Abstract: Rhizoctonia solani agglutinin (RSA) is a 15.5-kDa lectin accumulated in the mycelium and sclerotia of the soil born plant pathogenic fungus R. solani. Although it is considered to serve as a storage protein and is implicated in fungal insecticidal activity, its physiological role remains unclear as a result of a lack of any structure/function relationship information. Glycan arrays showed that RSA displays high selectivity towards terminal nonreducing N-acetylgalactosamine residues. We determined the amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In accordance with our study, fungal lectins have been previously detected in the mycelium and sclerotia of R. solani strains of different anastomosis groups (Kellens and Peumans 1991;Mghalu et al 2004) with a reported role in fungal growth and development (Leonidas et al 2007). Additionally, R. solani lectins were revealed to act as storage proteins (Skamnaki et al 2013). The down-regulation of R. solani AG-3 Rs114 lectins Fig.…”
Section: Carbohydrate-binding Genesmentioning
confidence: 96%
“…In accordance with our study, fungal lectins have been previously detected in the mycelium and sclerotia of R. solani strains of different anastomosis groups (Kellens and Peumans 1991;Mghalu et al 2004) with a reported role in fungal growth and development (Leonidas et al 2007). Additionally, R. solani lectins were revealed to act as storage proteins (Skamnaki et al 2013). The down-regulation of R. solani AG-3 Rs114 lectins Fig.…”
Section: Carbohydrate-binding Genesmentioning
confidence: 96%
“…Homodimer 4 Gal na Entomotoxic (Hamshou et al 2013;Hamshou et al 2010b;Hamshou et al 2012;Skamnaki et al 2013) Bleuler-Martinez et al 2011;Fujihashi et al 2003;Fukumori et al 1990;Kochibe and Furukawa 1980;Olausson et al 2010;Olausson et al 2008;Tateno et al 2009;Wimmerova et al 2003) GlcNAc-β1,4-X na nd (Cioci et al 2006;Ueda et al 1999a;Ueda et al 2002;Ueda et al 1999b;Ueda et al 2003) Entomotoxic (Birck et al 2004;Bleuler-Martinez et al 2011;Damian et al 2005;Francis et al 2003;Jaber et al 2008;Jaber et al 2007;…”
Section: β-Trefoilmentioning
confidence: 99%
“…While galectins bind linear glycans in a groove parallel to the protein surface, β-trefoil-type lectins bind them in a perpendicular orientation, in which only the non-reducing end of the glycan interacts with the binding pocket. All these proteins assemble to homodimers but, interestingly, each protein uses a different interface for dimer formation (Bovi et al 2013;Pohleven et al 2012;Schubert et al 2012;Skamnaki et al 2013;Sulzenbacher et al 2010;Žurga et al 2014).…”
Section: β-Trefoil-type Lectinsmentioning
confidence: 99%
“…Their expression observed in our study suggests a possible role in mycoparasitism, complementing the classical GH activity which is known to be involved. The carbohydrate binding module Family 13 gene encodes a protein with a domain related to lectins, which, in Rhizoctonia solani , is implicated in fungal insecticidal activity [33]. Our expression data suggest that this gene is related to the lectins and may play a role mediating the physical contact with the host and elicitation of the signaling cascade comprising G-proteins and MAPKs.…”
Section: Resultsmentioning
confidence: 97%